Decision Making with Naive Advice - Schotter, Andrew (American Economic Review, 2003)
Abstract In many of the decisions we make we rely on the advice of others who have preceded us. For example, before we buy a car, choose a dentist, choose a spouse, find a school for our children, sign on to a retirement plan, etc. we usually ask the advice of others who have experience with such decisions. The same is true when we make major financial decisions. Here people easily take advice from their fellow workers or relatives as to how to choose stock, balance a portfolio, or save for their child’s education. Although some advice we get is from experts, most of the time we make our decisions relying only on the rather uninformed word-of-mouth advice we get from our friends or neighbors. We call this ?aive advice? In this paper I will outline a set of experimental results that indicate that word-of-mouth advice is a very powerful force in shaping the decisions that people make and tends to push those decisions in the direction of the predictions of the rational theory.